Water quality characteristics and profiles in a developing urban catchment / Hasnaliza Aini Abd Talib - Abd Talib, Hasnaliza Aini (2008)
Increasing development and urbanization have made urban runoff a major problem both from the perspective of the flow quantities and qualities. The quantities and qualities of urban runoff depend on catchment characteristics. In Malaysia, urban drainage systems are designed to convey excess water to receiving water bodies such as lakes and rivers during wet weather flows. However, there is significant flow during dry weather due to discharges of grey water from residential, commercial and construction premises. This study focuses mainly on establishing pollutant characteristics and profiles in an urban drainage system for a developing catchment under dry weather flow condition. A 587.7 m drainage stretch in Section 7, Shah Alam was selected as the study stretch. The study subcatchment consists of housing areas, construction sites and also green areas. Samples were collected manually and were analysed in accordance to Standard Methods 1998. Collected samples were analysed for pH, temperature and also concentrations of organics, anions, cations and heavy metals elements. From the study, the pollutant concentrations ascertained were not normally distributed. The ranges established were pH (7.27-8.39), temperature (31-34.3°C), organic pollutants (5-50 mg/L), anions (0-34.844 mg/L), cations (013.618 mg/L) and heavy metals (0-1.352 mg/L). There were four pollutant profiles observed, i.e., decrease of pollutants concentrations at the middle point and increase towards the last point, pollutants concentrations increased at the middle point but decreased as it reached the last point, the concentrations of pollutants increased along the study stretch and pollutants concentrations decreased through out the study stretch. It was found that, only lead and cadmium concentrations will lead to further deterioration of Sungai Klang; and the pollutant trend depends on concentrations of pollutants in the mainstream and water discharging through inlets.